Whole genome sequencing and phylogenetic analysis of West Nile viruses from animals in New England, United States, 2021 - Hyeon, Ji-Yeon; Helal, Zeinab H.; Appel, Allison; Tocco, Natalie; Hunt, Amelia; Lee, Dong-Hun; Risatti, Guillermo R. (Frontiers in Veterinary Science, 2023)
West Nile virus is a mosquito-borne Flavivirus which is the leading cause of global arboviral encephalitis. We sequenced WNVs from an American crow found in Connecticut and an alpaca found in Massachusetts which were submitted to the Connecticut Veterinary Medical Diagnostic Laboratory (CVMDL). We report here the complete protein-coding sequences (CDS) of the WNVs (WNV 21-3957/USA CT/Crow/2021 and WNV 21-3782/USA MA/Alpaca/2021) and their phylogenetic relationship with other WNVs recovered from across the United States. In the phylogenetic analysis, the WNVs from this study belonged to the WNV lineage 1. The WNV 21-3957/USA CT/Crow/2021 clustered with WNVs from a mosquito and birds in New York during 2007-2013. Interestingly, the virus detected in the alpaca, WNV 21-3782/USA MA/Alpaca/2021 clustered with WNVs from mosquitos in New York, Texas, and Arizona during 2012-2016. The genetic differences between the viruses detected during the same season in an American crow and an alpaca suggest that vector-host feeding preferences are most likely driving viral transmission. The CDS of the WNVs and their phylogenetic relationships with other WNVs established in this study would be useful as reference data for future investigations on WNVs. Seasonal surveillance of WNV in birds and mammals and the genetic characterization of detected viruses are necessary to monitor patterns of disease presentations and viral evolution within a geographical area.